Decolonizing Ecotheology: Dayak Ecological Knowledge and the Recontextualization of Sean McDonagh’s Thought - Dismas Kwirinus; Edison Tinambunan; Fransiskus Emanuel; Heribertus Peri (Jurnal Studi Agama dan Masyarakat, 2026)
The ecological crisis in West Kalimantan reflects not only environmental degradation caused by extractive development, but also the marginalization of Indigenous ecological knowledge and authority. The study aimed to examine Sean McDonagh’s ecotheology in critical dialogue with Dayak Kanayatn ecological-spiritual narratives to assess its relevance and limitations for developing a contextual ecotheology. The particular study adopted a qualitative critical-hermeneutical design. Data were collected through textual analysis of Sean McDonagh’s major works, a review of relevant literature on ecotheology and Indigenous ecological knowledge, and limited field-based materials consisting of Dayak Kanayatn oral narratives and documentation of ecological-spiritual practices in Lingga Village, West Kalimantan. The data were analyzed through thematic reading, contextual hermeneutics, and critical discourse analysis. The findings showed that McDonagh’s critique of capitalism, anthropocentrism, and ecological injustice remains significant, yet his framework requires recontextualization when read through Dayak cosmology. Concepts and practices such as Jubata, Nyangahatn, customary norms, sacred landscapes, and human–nature–spirit relations revealed that ecological responsibility was rooted in lived cosmology, reciprocity, care, and communal practice. The study concluded that Dayak ecological knowledge offers a critical correction to global ecotheology by shifting the focus from external stewardship toward locally grounded ecological responsibility.